O processamento fonológico e o seu papel nos transtornos da aprendizagem da leitura e da matemática - Caroline Greiner de Magalhães (2017)
Recently, some researchers (e.g., De Smedt et al., 2010 and Hecht et al., 2001) have argued that deficits in phonological processing are associated with both reading and math disabilities. The present study examined this hypothesis. In particular, the study examined whether and, to what extent, deficits in the components of phonological processing, namely, phonemic awareness (CF), rapid serial naming (NSR) and verbal memory (MV), characterize children with isolated math difficulties. The study included 114 children enrolled in 4th and 5th grade classrooms of private schools in the metropolitan region of Belo Horizonte, MG, Brazil (mean age = 121.89 months; SD = 8.48), divided in four groups, according to their performance on standardized tests of reading, spelling and mathematics: 22 with isolated reading and spelling difficulties (DLE), 19 with isolated math difficulties (DM), 16 with difficulties in reading, spelling, and mathematics (DLEM), and 57 without learning difficulties (controls). In addition to tests of reading, spelling, and mathematics, the children completed tests of verbal and non-verbal intelligence, CF, NSR, and MV. Results revealed the presence of MV deficits in both the children with reading and spelling difficulties and in those with math difficulties, regardless of whether their learning difficulties were isolated or not. On the other hand, deficits in CF and NSR were found only among the children with reading difficulties, that is, in the children with either DLE or DLEM. Importantly, contrary to what was observed for CF and NSR, the MV deficit in the comorbid group was not additive, but equivalent to that found in the groups with isolated disorders of reading or mathematics, suggesting that deficits in MV, but not in CF or NSR, are shared by reading and math learning disorders. Consistent with these results, multiple regression analyzes with all the children revealed that, along with variations in verbal intelligence, variations in CF and NSR contributed significantly and independently to variations in reading and spelling ability, while variations in mathematics were explained by variations in nonverbal intelligence, verbal intelligence, and MV. These results are discussed in the light of B. Pennington’ multiple deficits framework.